Field reports contributed by Thomas H. Kent, December 9, 1998 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1998)
Fall report of birds and locations contributed by Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed